Performance and emission characteristic of compression ignition engine using blend of diesel and canola oil - M. F., Fariz; C. K., Ihsan; M. M., Noor; K., Kadirgama; D., Ramasamy; M. M., Rahman; A. T., Hoang (2018)
This study presents an investigation of engine running on diesel in order to determine the engine operating characteristic and exhaust emissions levels when using diesel and canola oil. The blend of canola and diesel consist of 5%, 10% and 15%. The engine coupled to dynamometer with 0% load condition for the test. The same method will be repeated for each fuel blend by keeping the same condition. The present studies contribute as an alternative fuel by using biofuel from non-edible for diesel engines with standard engine parts.